EARice10: a 10 m resolution annual rice distribution map of East Asia for 2023 - M. Song; M. Song; M. Song; L. Xu; L. Xu; J. Ge; J. Ge; J. Ge; H. Zhang; H. Zhang; H. Zhang; L. Zuo; et al. (Earth System Science Data)
Timely and accurate high-resolution annual mapping of rice distribution is essential for food security, greenhouse gas emissions assessment, and support of sustainable development goals. East Asia (EA), a major global rice-producing region, accounts for approximately 29.3 % of the world's rice production. Therefore, to acquire the latest rice distribution of the EA, this study proposed a novel rice distribution mapping method based on the Google Earth Engine (GEE) platform, producing a 10 m resolution annual rice distribution map (EARice10) of EA for 2023. A new synthetic aperture radar (SAR)-based rice distribution mapping index (SRMI) was firstly proposed and combined with optical indices to generate representative rice samples. In addition, a stacking-based optical–SAR adaptive fusion model was designed to fully integrate the features of Sentinel-1 and Sentinel-2 data for high-precision rice mapping in EA. The accuracy of EARice10 was evaluated using more than 90 000 validation samples and achieved an overall accuracy of 90.48 %, with both the user accuracy and the producer accuracy exceeding 90 %. The reliability of the product was verified by R2 values ranging between 0.94 and 0.98 with respect to official statistics and between 0.79 and 0.98 with respect to previous rice mapping products. EARice10 is accessible at https://doi.org/10.5281/zenodo.13118409 (Song et al., 2024).